ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH DI LINGKUNGAN KANTOR PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PROVINSI KALIMANTAN TIMUR - -, Dondy Indraprakoso (EKONOMIA, 2019)
The objectives to be achieved in this research is to know the achievement level of maturity of SPIP application as the provision in Indicator of Performance of National Medium Term Development Plan (RPJMN) 2015-2019. The formulation of the problem from this research is